Cultivation of Chlorella vulgaris in Sequential Flow Photobioreactor System: Influence of Recycled Culture Medium on Growth, Lipid and Protein Content. Issue 1 (April 2021) - Dasan, Yaleeni Kanna; Lam, Man Kee; Yusup, Suzana; Lim, Jun Wei; Lee, Keat Teong; Show, Pau Loke; Tan, Inn Shi; Yew Foo, Henry Chee
Abstract: In the present work, the reusability of culture medium to grow Chlorella vulgaris was examined in an effort to reduce the freshwater footprint of microalgae cultivation. The microalagae was cultivated in a sequential-flow system equipped with five photobioreactors connected in series. Furthermore, the effect of recycled culture medium without additional nutrients on the growth, lipid and protein content of microalgae was evaluated under optimized cultivation conditions. Experimental results showed that biomass concentration and growth rate reduced when the recycled culture medium was used. The maximum biomass concentration was achieved in the fresh medium with a total biomass yield of 1.42 g/L. Meanwhile, lipid content was found to increase when the microalgae was cultivated in the recycled medium, in which the highest lipid content (58.01 wt.%) was attained from photobioreactor 5 (cycle 2). On the contrary, the protein content (11.98 wt.%) of the microalgae in the recycled medium was considerably lower than the fresh medium (49.20 wt.%). These results suggested that the reuse of culture medium to grow microalgae is possible, however, it has a significant impact on the biochemical compositions of Chlorella vulgaris . Therefore, it is important to determine the desired product prior to reusing the medium for subsequent cultivation process.